Electrosprayed cysteine-functionalized degradable amphiphilic block copolymer microparticles for low pH-triggered drug delivery. Issue 42 (16th October 2019) - Finnegan, Marie; Mallon, Gerard; Leach, Adam; Themistou, Efrosyni
Abstract : Fluorescent dye encapsulation and release using mucoadhesive degradable thiol-functionalized amphiphilic block copolymer microparticles prepared by electrospraying. Abstract : Thiol-functionalized polymeric microparticles have attracted interest as mucoadhesive drug delivery formulations. However, new approaches are needed to optimize the preparation of these systems for patient use. Here, N -hydroxysuccinimide (NHS)-functionalized degradable amphiphilic diblock copolymer microparticles are prepared via electrospraying and subsequently functionalized with thiols. A poly(l -lactide)- b -poly(2-(methacryloyloxy)ethyl phosphorylcholine)- st -(methacrylic acid NHS ester) (PLA- b -P(MPC- st -NHSMA)) diblock copolymer was synthesized by sequential ring opening polymerization and reversible addition–fragmentation chain transfer polymerization. One-step microparticle preparation and rhodamine B encapsulation were performed by electrospraying. Cysteine attachment to the microparticle surface via succinimide chemistry resulted in their functionalization with thiol groups. These reacted with fluorescein isothiocyanate (FITC) to provide a fluorescent tag, proving the thiol reactivity. Highly controlled release of the dye was observed at low pH over a period of 89 days. These thiol-functionalized degradable microparticles are expected to have enhanced mucoadhesive properties with high potential for use as next-generation formulations at low pH, such as gastric, drug delivery.